Historical analysis of storm events: case studies in France, England, Portugal and Italy - Garnier, E. (2019)
An historical analysis of the occurrence of storms and their damage intensity is presented. The work analysed historical large-scale events from The Middle Ages to the 1960s at case study sites along the coasts of North Norfolk (UK); Charente-Maritime and Vendée (France); Cinque Terre-Liguria coast (Italy); Emilia-Romagna coast (Italy) and Ria Formosa (Portugal). The work presented here used a database of events built by the RISC-KIT project, including the characteristics of the storms as well as recorded human impacts. Historical records can provide an important test bed to complement the statistical analysis of the return period of events based on measurements and provide important indicators of past events and their impact that are no longer within the historical memories of resident populations and coastal managers.